Affective domain and mathematics in Early Childhood Education: an emotional perspective (Edma 0-6: Educación Matemática en la Infancia, 2025)
The consideration of emotions in mathematics education and their proper integration into the cognition-emotion binomial are necessary conditions for ensuring efficient and inclusive teaching-learning processes. However, the attention paid to this issue in the context of early childhood education has been minimal compared to other stages. This study carries out a diagnosis of the situation through a bibliometric analysis of high-impact international research on the affective domain in mathematics in early childhood education, together with research based on a mixed exploratory approach, through which the emotions of 5-6-year-old students are analysed to determine the relationship between emotions and mathematical concepts. The results show that the research community is still in the early stages of paying attention to affect in mathematics in early childhood education, as well as the strong presence of positive emotions such as joy in most of the relationships analysed. Finally, some general recommendations for action are offered, aimed at families, teachers and educational institutions.
Keywords: Emotions; Attitudes; Mathematics; Early childhood education; Affects